PRINSIP KEMANDIRIAN EKONOMI PERSPEKTIF RASULULLAH - Imron Rosadi; Lutfiyanto (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2025)
Rasulullah is a leader of the ummah throughout the world, where he is a role model in worship, social interaction with others or in doing charity, because everything that originates from Rasulullah is sunnah in accordance with what was conveyed by hadith scholars, which means "everything that is attributed to the Prophet Muhammad SAW is sunnah, whether in the form of words, deeds, taqrir (rule of law), khuluqiyyah (personality) and khalqiyyah (physical) of him. Because something that comes from the Messenger of Allah is essentially from Allah, which in this case is emphasized which means "And he did not speak from his desires, but rather a revelation that was revealed." One of the things that is no less important to study is his principle of economic independence in living his life, so that we can take intifa' (benefits) from him, to use as a principle in living this life and which is no less important so that we always follow the sunnah in aspects of our life.